The Implications of USA/Israeli War with Iran on Global Peace - Joseph O. Odama; Mukhtar Imam; Francis C. Okpo (Bulletin of Islamic Research, 2026)
Purpose – This study examines the structural dynamics of the military confrontation involving the United States, Israel, and Iran during *Operation Epic Fury* and evaluates its implications for the evolving international order. Drawing on hegemonic transition theory and alliance politics, the study investigates whether the conflict represents a precursor to systemic great-power war or a catalyst for the transformation from a unipolar to a multipolar global system. Design/methodology/approach – The research adopts a qualitative case study approach based on documentary analysis. It integrates theoretical perspectives from hegemonic transition theory and alliance politics to interpret geopolitical developments, alliance behavior, and strategic interactions among major powers. Policy statements, strategic documents, and contemporary geopolitical developments are analyzed to identify emerging patterns in the international system. Findings – The analysis indicates that the conflict has intensified strategic realignments rather than creating the conditions for a conventional global war. The crisis has exposed growing divergences within the transatlantic alliance, reflecting increasing strategic autonomy among several European states. At the same time, Russia and China have adopted distinct strategic responses shaped by their respective geopolitical and economic interests rather than forming a unified anti-Western bloc. The disruption of energy supply routes has further demonstrated the vulnerability of the global economy to regional conflicts, reinforcing the strategic significance of maritime chokepoints and energy security. Research implications/limitations – The study is limited to a single geopolitical case and relies on documentary evidence available during the period examined. Because international crises evolve rapidly, subsequent developments may alter strategic assessments. Future research should incorporate longitudinal analysis and comparative studies of major-power crises. Originality/value – This study contributes to contemporary international relations scholarship by integrating hegemonic transition theory with alliance politics to explain how regional conflicts can accelerate systemic transformation. It argues that the emerging international order is characterized less by renewed bipolarity than by the growing influence of multiple regional powers operating within an increasingly multipolar strategic environment.